2019
DOI: 10.1111/ahe.12465
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometrical and stereological study of the oesophagus in the adult male Persian squirrel (Sciurus anomalus)

Abstract: The Persian squirrel (Sciurus anomalus) is habitat in the Middle East countries and feed on pine acorns and other seeds. The present study was carried out to investigate the histological and volumetric features of the oesophagus in Persian squirrels. Five adult male Persian squirrels were included in the study. The cervical, thoracic and abdominal oesophagus of all subjects were processed routinely and sectioned in a serial manner. Then, the total volume of the oesophagus and its different layers were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…The oesophagus of the southern white‐breasted hedgehog had entirely a non‐keratinized stratified squamous epithelium. This observation is consistent with that reported in the rabbit (Selim et al, 2017), Persian squirrel (Goodarzi et al, 2019), and African giant rat (Nzalak et al, 2010), but is contrary to those observed in the guinea pig (Berghes et al, 2011). In comparison with other mammals, herbivorous mammals such as horses, cows, and camels had a keratinized oesophageal epithelium (Eurell & Frappier, 2006; Nabipour et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The oesophagus of the southern white‐breasted hedgehog had entirely a non‐keratinized stratified squamous epithelium. This observation is consistent with that reported in the rabbit (Selim et al, 2017), Persian squirrel (Goodarzi et al, 2019), and African giant rat (Nzalak et al, 2010), but is contrary to those observed in the guinea pig (Berghes et al, 2011). In comparison with other mammals, herbivorous mammals such as horses, cows, and camels had a keratinized oesophageal epithelium (Eurell & Frappier, 2006; Nabipour et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in agreement with observations in the dog and ruminants (Eurell & Frappier, 2006). Similar findings were also reported in rodent species such as guinea pigs (Berghes et al, 2011), African tree Squirrel (Igbokwe & Obinna, 2016), and Persian squirrel (Goodarzi et al, 2019). However, tunica muscularis can be composed of three muscular layers in the rabbit (Mohammadpour & Darvishzadeh, 2014) and guinea pig (Francis, 1974).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Literature review shows that few studies performed on the anatomical or histological feature of the gastrointestinal tract including topography and gross anatomy of the abdominal gastrointestinal tract (Tootian et al, 2013) and histochemical properties of the small intestine (Sadeghinezhad et al, 2012). Recently, Goodarzi et al (2019) described the histological and stereological properties of the esophagus in this species.. However, the histological features of the stomach in this species remains unclear.…”
Section: Introductionmentioning
confidence: 99%